Nickel (II) Complexes with Pentane-2,4-dione Bis(4-allylthiosemicarbazone) [Articol] - Gulea, Aurelian; Graur, Vasilii; Ciumacov, Iurie; Petrenko, Peter; Garbuz, Olga; Țapcov, Victor; Gudumac, Valentin (My University, 2020)
Reaction of pentane-2,4-dione with N-(prop-2-en-1-yl)hydrazinecarbothioamide at a 1: 2 molar ratio in ethanol resulted in the formation of a pyrazole derivative. The latter reacted with nickel perchlorate at a 1: 1 molar ratio to form the nickel complex with pentane-2,4-dione bis(4-allylthiosemicarbazone). The same type of nickel complex was obtained as a result of N-(prop-2-en-1-yl)hydrazinecarbothioamide reaction with pentane-2,4-dione and nickel nitrate at a 2: 1: 1 molar ratio. Antimicrobial, antifungal, antioxidant, and anticancer activities of the obtained compounds were studied.
Keywords: Ni(II) coordination compounds; acetylacetone bis(4-allylthiosemicarbazone); anticancer activity